EDUCATIONAL SUPERVISION OF THE EFFORTS MADE MADRASAH FAMILY IN MTs AL-IHSAN IN INCREASING THE PROFESSIONALISM OF TEACHERS TEACHER PROFESSIONALISM - adiyono; Ana Saraya; Annisa Mardhatillah; Elisa Novianur Fitriani (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to describe all the efforts made by the principal as a supervisor in supervising teachers at MTs Al-Ihsan, Tanah Grogot. This research method uses qualitative research. The research data were obtained from an interview with the principal of MTs Al-Ihsan, Tanah Grogot. Interviews were conducted in order to obtain information regarding how and what the principal of the school did in supervising teachers for the realization of professional teachers.The results of this interview obtained regarding the program carried out by the principal in carrying out supervision, the stages of carrying out supervision, the types of supervision that have been carried out, the time of supervision, the supporting factors for carrying out supervision, the inhibiting factors for carrying out supervision, phased evaluation actions for teachers, evaluation results that are still not optimal, teacher competencies to be achieved, supervision program planning to improve teacher professionalism, solutions from the school principal if the program does not go well, as well as matters that determine the success of the implementation of supervision.